Analisa Performansi Protokol TCP, UDP dan SCTP Pada Lalu Lintas Multimedia - Yesi Mardiana; Julidian Sahputra (UNIVED Press, 2017)
This study aims to analyze Performance of TCP, UDP and SCTP Protocol on Multimedia Traffic. The TCP (Transmission Control Protocol) protocol, UDP (User Datagram Protocol) and SCTP (Stream Control Transmission Protocol) reside on the same layer in the OSI-Layer at the Transport layer that controls the flow of data, data packets and so on. This research uses windows operating system and Softperfect Network Protocol Analyzer software. Where network analysis software has a complete feature such as can filter almost all the protocol on the OSI-Layer, has a report of easy to read results and so forth. From the test results conducted for three days by analyzing the online and offline way obtained SCTP protocol results both for Multimedia activities but can not be used simultaneously with other activities (such as video conversations). for everyday activities should use TCP and UDP protocol because it tends to be stable.Keyword : TCP, UDP, SCTP